2018
DOI: 10.5539/ijbm.v13n9p189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Psychological Capital and Perceived Organizational Support on Subjective Career Success: The Mediating Role of Women's Career Adaptability in the Saudi Context

Abstract: This paper is the first to explore predictors' keys of career adaptability and subjective career success in the Saudi context. Many employees, especially women, are facing several challenges in their work, and career adaptability is a way to overcome these difficulties to reach the career success. This research investigated the mediating role of career adaptability (CA) in the relation between both psychological capital (PsCap) and perceived organizational support (POS), as predictors of CA, and subjective car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
1
4
0
2
Order By: Relevance
“…The study’s findings were in line with Eskildsen and Dahlgaard (2000) and Tang et al (2019), showing the influence of psychological capital on employees’ job satisfaction unlike the study of Idris and Manganaro (2017) that reported no significant relationship between psychological capital and employees’ job satisfaction. Other studies such as Abosaif (2018), Aljaghthami and Noormala (2016), Ibrahim and Amari (2018), and Saad Alkahtani et al (2020) also confirmed the positive impact of psychological capital on various constructs. Extant literature has also revealed psychological capital is narrowly related to their work performance (Avey et al, 2008), positivity, and creativity (Rego et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…The study’s findings were in line with Eskildsen and Dahlgaard (2000) and Tang et al (2019), showing the influence of psychological capital on employees’ job satisfaction unlike the study of Idris and Manganaro (2017) that reported no significant relationship between psychological capital and employees’ job satisfaction. Other studies such as Abosaif (2018), Aljaghthami and Noormala (2016), Ibrahim and Amari (2018), and Saad Alkahtani et al (2020) also confirmed the positive impact of psychological capital on various constructs. Extant literature has also revealed psychological capital is narrowly related to their work performance (Avey et al, 2008), positivity, and creativity (Rego et al, 2012).…”
Section: Discussionsupporting
confidence: 57%
“…They added that culture and context may limit adaptability. The career literature is replete with the CAAS being researched in various countries, for example, China (Guan et al, 2016), Saudi Arabia (Ibrahim & Amari, 2018), and Turkey (Işık et al, 2018), suggesting that country of participants should be considered as a moderator.…”
Section: Methodsmentioning
confidence: 99%
“…Pengetahuan dan keterampilan yang dipelajari individu sebelumnya akan digunakan dalam proses kerja selama individu menjalani kariernya. Selanjutnya, kemampuan individu untuk beradaptasi dalam menjalani kariernya atau adaptabilitas karier juga merupakan salah satu prediktor penting pada kesuksesan karier subjektif (Zacher, 2014;Ibrahim & Amari, 2018). Savickas (2005) menegaskan bahwa adaptasi yang berkelanjutan terhadap lingkungan kerja bersifat penting dalam pencapaian kesuksesan karier.…”
Section: Faktor-faktor Yang Memengaruhiunclassified